Novel Vascular Malformation in an Affected Newborn with Deletion Del(4)(q31.3) - Norma Elena de León Ojeda; Michel Soriano-Torres; Mercedes J. Cabrera; Dunia Bárbara Benítez Ramos (Case Reports in Genetics)
We report on a newborn male patient with a terminal deletion in the long arm of the chromosome 4 with a congenital heart defect unreported before in association with this syndrome. The patient had multiple congenital anomalies including a pointed duplicated fingernail, low set posteriorly rotated ears, large anterior fontanel, micrognathia, glabellar capillary vascular malformation, and Interrupted Aortic Arch type C. The patient died due to multiple congenital malformations; a peripheral chromosome analysis showed 46, XY, del(4)(q31.3) de novo. The only reported case with the same deletion was a male newborn that exhibited the pattern of minor anomalies of deletion 4q31 syndrome. The parents were cytogenetically normal. We compare clinical signs to other cases with a deletion in long arm of chromosome 4.